Design wave height and wave period of sea waves at Digha (MAUSAM, 1978)
The most probable height and period or the waves which will occur in any given length of time have been determined from systematic, instrumental records of sea. waves at Digha. In determining the design wave height and wave period the method as suggested by Draper (1963) has been used. Cumulative distribution of the highest and the significant wave heights and the distribution of wave periods in percentage of occurrence have also been presented in this paper.